2011
DOI: 10.1016/j.jsps.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid HPLC method for simultaneous determination of atenolol and chlorthalidone in spiked human plasma

Abstract: A simple, sensitive and rapid chromatographic method was developed and validated for the simultaneous quantification of atenolol and chlorthalidone in human plasma using hydrochlorothiazide as internal standard (IS). The method utilized proteins precipitation with acetonitril as the only sample preparation involved prior to reverse phase-HPLC. The analytes were chromatographed on Shim-pack cyanopropyl column with isocratic elution with 10 mM KH2PO4 (pH 6.0) - methanol (70:30, v/v) at ambient temperature with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…[3][4][5] Literature review reveals that HPLC. [21][22][23][24] UV [25] spectrophotometric methods have been reported for quantification of CHLO in pharmaceutical dosage form. Literature review reveals that HPTLC [26] HPLC [27][28][29][30] methods have been reported for simultaneous estimation of TEL and CHLO in dosage forms however, so far, no method was reported qualitative estimation of any degradation product with the simultaneous determination of Telmisartan (TEL) and Chlorthalidone (CHLO) in bulk API and FDC.…”
Section: Pharmacopoeia (Ip) British Pharmacopoeia (Bp) and Us Pharmentioning
confidence: 99%
“…[3][4][5] Literature review reveals that HPLC. [21][22][23][24] UV [25] spectrophotometric methods have been reported for quantification of CHLO in pharmaceutical dosage form. Literature review reveals that HPTLC [26] HPLC [27][28][29][30] methods have been reported for simultaneous estimation of TEL and CHLO in dosage forms however, so far, no method was reported qualitative estimation of any degradation product with the simultaneous determination of Telmisartan (TEL) and Chlorthalidone (CHLO) in bulk API and FDC.…”
Section: Pharmacopoeia (Ip) British Pharmacopoeia (Bp) and Us Pharmentioning
confidence: 99%
“…Nowadays, health products are widely adopted as supplementary antihypertensive strategy, while the adulteration product has been an emerging issue of concern to the public health. To a patient undergoing therapeutic treatment, misuse of adulterated health product may result in unexpected changes in the blood pressure and might cause harmful effects to patients [2,11]. Consequently, monitoring the qualities of health product in the market is a work of great importance.…”
Section: A Venetum L (Av) Tea Samplesmentioning
confidence: 99%
“…In principle, the joint of complementary medicines can not only help to meet the target blood pressure, but also decrease the morbidity and mortality of complications. In practice, many doctors as well as the World Health Organization have been beginning to detector (UV) [10][11][12][13], fluorescence detector (FD) [14,15], amperometric detector (AD) [16], diode array detector (DAD) [17][18][19] and mass spectrometry (MS) [20][21][22]. However, most works have been focused on quantifying a small amount or one kind of antihypertensives in biological matrix or Chinese herbal matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods have been reported for the determination of atenolol in human plasma, urine, or pharmaceutical preparations, such as high-performance liquid chromatography [5][6][7][8][9], gas chromatography [10], liquid chromatography [11,12]. Other techniques include voltammetric [13][14][15], electrophoresis [16,17], chemiluminescence [18][19][20], spectrofluorimetric [21], ultraviolet and visible spectrophotometry [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%